WNT6 is a novel oncogenic prognostic biomarker in human glioblastoma - Gonçalves, Céline S. (2018)
Glioblastoma (GBM) is a universally fatal brain cancer, for which novel therapies targeting specific underlying oncogenic events are urgently needed. While the WNT pathway has been shown to be frequently activated in GBM, constituting a potential therapeutic target, the relevance of WNT6, an activator of this pathway, remains unknown. Methods: WNT6 protein and mRNA levels were evaluated in GBM. WNT6 levels were silenced or overexpressed in GBM cells to assess functional effects in vitro and in vivo. Phospho-kinase arrays and TCF/LEF reporter assays were used to identify WNT6-signaling pathways, and significant associations with stem cell features and cancer-related pathways were validated in patients. Survival analyses were performed with Cox regression and Log-rank tests. Meta-analyses were used to calculate the estimated pooled effect. Results: We show that WNT6 is significantly overexpressed in GBMs, as compared to lower-grade gliomas and normal brain, at mRNA and protein levels. Functionally, WNT6 increases typical oncogenic activities in GBM cells, including viability, proliferation, glioma stem cell capacity, invasion, migration, and resistance to temozolomide chemotherapy. Concordantly, in in vivo orthotopic GBM mice models, using both overexpressing and silencing models, WNT6 expression was associated with shorter overall survival, and increased features of tumor aggressiveness. Mechanistically, WNT6 contributes to activate typical oncogenic pathways, including Src and STAT, which intertwined with the WNT pathway may be critical effectors of WNT6-associated aggressiveness in GBM. Clinically, we establish WNT6 as an independent prognostic biomarker of shorter survival in GBM patients from several independent cohorts. Conclusion: Our findings establish WNT6 as a novel oncogene in GBM, opening opportunities to develop more rational therapies to treat this highly aggressive tumor.